Analysis of HOTS and LOTS of instructional questions in the English textbook "When English Rings a Bell" for grade VIII - Surono Surono; Bambang Widi Pratolo; Siti Latifah Hanun (Universitas Ahmad Dahlan, 2023)
English textbooks have an essential role in learning English subjects for students in junior high school, so the quality of textbooks must be of high quality. To make students master English language skills, they need a good quality of textbooks to improve their critical thinking skills. This research aims to find out the representation of higher order thinking skills (HOTS) and lower order thinking skills (LOTS) and the appearance frequency in the instructional questions in English textbook entitled "When English Rings A Bell" grade VIII. This study used a content analysis with qualitative approach. Six chapters of the textbook were taken as the sample. Observation and note-taking techniques were used to collect the data using observation sheet. The data were analyzed by using Miles's et al. model regarding coding method. The research findings showed that chapters I, VI, and VII represented LOTS with the most dominant in remembering and applying. Meanwhile, the appearance of LOTS and HOTS in chapters V and XII looked nearly in balance dominating the verb remembering for LOTS and the verbs evaluating and creating for HOTS. The realization of HOTS in the chapters was less than LOTS, except chapter XIII. After the instructional questions in all activities were categorized, the distribution of LOTS in the textbook appeared in 66 (58%) and HOTS in 47 questions (42%). It is concluded that the textbook distributed less evenly in HOTS and LOTS composition. It implies that the textbook still focuses on LOTS. It is recommended that the authors of the textbook balance the HOTS and LOTS in the instructional questions proportionally to encourage students to think critically. Teachers should creatively modify the instructional questions to meet the balance.